MANAGEMENT OF LEISURE ACTIVITIES (Fiep Bulletin - online, 2014)
In the fi eld of physical activities and sport a strategic aim of us is to identify and apply in long term perspective a system ofsupport to different forms and levels of sports. most important priorities are physical activities of children and a national sport representation. this system of support should be effective and based on ethical principles. the core priority of us in that fi eld is increasing physical activity by children. intention of the scientifi c project was to verify a system of organization and fi nancing of physical activities. to detect the impact of the state subsidy on increasing participation of target group in physical activities offered by different sports organizations. Also identify mechanisms, which are restraining smooth and transparent organization and fi nancing of physical and sports activities during project. increasing of the subsidy, in form of vouchers, was an experimental factor in this project. sport voucher system was built according principles of liberality and free market mechanism. During this project we received data indicating option to raise number of pupils, which are using physical activities in their leisure time. new system needs to global implementation a few modifi cations in order to secure smooth, transparent and acceptable process.
Keywords: physical activities; leisure sport; voucher; fi nancial support